Aquaculture practices among the fish farmers of Bhaluka upazila, Mymensingh - Scenario from a decade and half ago - Hasan, M Maruf; Zaman, Maria; Naser, Md Niamul (Dhaka University Journal of Biological Sciences, 2022)
Mymensingh is the top inland aquaculture producer in Bangladesh. This study was undertaken to identify the barriers to develop earthen pond fish farming entrepreneurship in Bhaluka Upazila, Mymensingh about a decade and half ago when the fish culture revolution has been started. In this study, fish farmers were selected randomly from three villages that followed mono or composite-fish culture in earthen pond environment. More than 14 species being cultured of which half of them were exotic. The feasibility of pond fish culture was found viable due to proper communication with Dhaka wholesale fish market along with other destinations. In addition, hatchery sources of fish fry and fingerling, access to fish feed and financial support were further encouraged farming these perishable items. Education level of farmers, lack of technical knowledge of fish culture, poor extension service and lack of information about the pond management were identified as the potential barriers for the improvement of fish farming entrepreneurship. The higher stocking density as well as poor water quality conditions were facilitated to lead lower fish production and profit. The small-scale farmers (47.79%) with higher stocking density had lower profit (Tk 1.44 /fish) and large-scale farmers (19.85%) with lower stocking density showed higher profit margin of Tk 3.53 /fish. Therefore, this study suggests the optimal fish stocking density in earthen pond fish farming system which could be augment the fish production and enhanced profitability. Dhaka Univ. J. Biol. Sci. 30(3 CSI): 499-509, 2022 (June)